Supporting informal communication in distributed engineering design teams - Törlind, Peter; Larsson, Andreas (Luleå tekniska universitet, Innovation och Design, 2002)
Successful teamwork in geographically distributed teams is highly dependent on tools that support informal communication, such as opportunistic and spontaneous interaction. Such informal communication is responsible for much of the information flow in an organization. This paper presents how informal communication was supported in the Distributed Team Innovation project, a joint product development effort between Luleå University of Technology, Stanford University and Volvo Car Corporation. A webbased Contact Portal was created in order to support informal communication and information sharing in a distributed engineering design team. The Contact Portal has been a valuable asset in the project, primarily because it combines several information channels; e-mail archives, awareness cameras, diaries, instant messaging, and SMS etcetera in one place. The Contact Portal was a natural starting point for initiating and maintaining contact with remote team members. The small window of opportunity made it difficult to continuously plan and hold formal meetings (videoconferences and telephone conferences), so the opportunistic interactions have been an important part of the information sharing in the project. Godkänd; 2002; Bibliografisk uppgift: 1 CD-ROM Kongress-Thema: Design in the E-commerce economy: design theory, methodology, tools and environment to support E-commerce-driven design and manufacturing; 20070328 (petert)